KAJIAN ETNOMATEMATIKA PADA PERMAINAN TRADISIONALMASYARAKAT ALOINDONU DAN INTEGRASINYA DALAM PEMBELAJARAN MATEMATIKA DI KABUPATEN ALOR - salim, halija; Likur, Fadhillah A. H.; Rahim, Nurdin (STKIP Muhammadiyah Kalabahi, 2026)
This study aims to describe ethnomathematics in the traditional games of the Aloindonu community and to find out how to integrate ethnomathematics in traditional games in mathematics learning in Aloindonu, Alor Regency. This research is very important to be carried out so that the generation in Aloindonu village does not forget traditional games which are local cultural heritage caused by modernization. This study uses a field research method approach or field research. The presence of the author as the main instrument in conducting observations in the village of Alila Selatan, the main objective is to observe and document the types of traditional games that are still played by children directly. Data collection in this study was carried out through observation, interviews, and documentation. Data analysis techniques start from the process of data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that traditional games such as Tibo' Afele (wood pry) contain elements of calculation, comparison, measurement and geometry. Hey Do' (jump rope) contains the concept of pattern measurement, geometry and calculation. Do' (senje) contains elements of measurement, pattern, and measurement. Gundu/marbles (Kuti Pot) contain aspects of counting, patterns, measurement, and geometry. And bekel balls (Loga) contain elements of calculation, patterns, measurement, and geometry. The results of this finding explain that traditional games found in Aloindonu village have relevant potential. In order to be used as an effective learning medium, this approach aims to make mathematical concepts more real and significant for students, while supporting the implementation of the Independent Curriculum which emphasizes environment-based learning and the preservation of local wisdom.